2019
DOI: 10.29219/fnr.v63.3603
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative and antidiabetic effects of germinated rough rice extract in 3T3-L1 adipocytes and C57BLKS/J-db/db mice

Abstract: BackgroundTo overcome disadvantages of germinated brown rice, we germinated rough rice and tested effects of its useful ingredients on prevention of diabetes.ObjectiveThis study investigated the in vitro antioxidant and in vivo antidiabetic effects of rough rice (Oryza sativa L.) with hulls, before and after germination. Rough rice was germinated for 4 days and extracted with water at 120°C.DesignThis study measured antioxidants and antioxidative effects and inhibitory activities against α-amylase and α-glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…The bulk density decreased significantly as the germination duration was increased and those germinated for 36 h were significantly lower than (p<0.05) those of the control. This could also be due to the breakdown of macromolecules by the enzymes involved in the germination process whose activity increased as the germination duration was increased [21,22]. This is in agreement with previous reports [23,24].…”
Section: Functional Properties As Affected By Milling and Germination...supporting
confidence: 91%
See 2 more Smart Citations
“…The bulk density decreased significantly as the germination duration was increased and those germinated for 36 h were significantly lower than (p<0.05) those of the control. This could also be due to the breakdown of macromolecules by the enzymes involved in the germination process whose activity increased as the germination duration was increased [21,22]. This is in agreement with previous reports [23,24].…”
Section: Functional Properties As Affected By Milling and Germination...supporting
confidence: 91%
“…The cooking time was also shorter in GBR samples than BR and this also was previously reported [32,34]. The reason for this could be due to modification of the rice kernel by the action of the enzymes during rice germination [22]. The change in the temperature of germination did not result in any significant effect (p<0.05) on the cooking time.…”
Section: Cooking Properties As Affected By Milling and Germination Co...supporting
confidence: 76%
See 1 more Smart Citation
“…In addition, the mice in group B, which had received the same dose of non-germinated adzuki beans, showed a poorer control of FBG than the mice in group TF3, which had been fed the highest dose of GABA-enriched germinated adzuki beans. These results implied that the hypoglycemic effect of TF3 was not due to the extra adzuki bean supplementation but the intrinsic activity of GABA in the germinated adzuki beans, and previous studies have also shown that the increased GABA content in germinated brown rice ( 28 ) and sprouted black rice ( 29 ) possibly played a significant role in the anti-diabetic properties attributed to these two cereal grains.…”
Section: Discussionmentioning
confidence: 58%
“…Adzuki bean contains a high amount of sodium glutamate (MSG), which is a good source of GABA, an earlier study has shown that germination treatment can increase GABA content in the bean ( 13 ), and dietary supplementation with GABA or GABA-rich foods is a common strategy for the treatment of T2DM. GABA-rich brown rice improves the blood glucose level of rats with T2DM ( 14 ) and has protective effects against liver and pancreatic injury ( 15 ). The dietary intake of sprouted black rice also helps to prevent and control T2DM ( 16 ).…”
Section: Introductionmentioning
confidence: 99%